Composite solid electrolyte and manufacturing method thereof

By introducing lithium lanthanum zirconium oxide powder and lithium phosphate-containing protective layer, or nanopowder, protective layer and fluorine-containing colloid into the solid electrolyte, the problem of high resistance value of solid electrolyte is solved, and efficient ion transfer and stable battery performance are achieved.

CN119833726APending Publication Date: 2025-04-15HON HAI PRECISION INDUSTRY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311318339.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional liquid electrolytes are unstable during use at high temperatures, prone to volatilization and leakage, and the resistance value of solid electrolytes is high, resulting in poor ion transfer rates.

Method used

Compound solid electrolytes are used, including lithium lanthanum zirconium oxide powder and lithium phosphate-containing protective layer, or lithium lanthanum zirconium oxide nanopowder, lithium phosphate-containing protective layer and fluorine-containing colloid, to form a protective layer through acid-base reaction to reduce the resistance value.

Benefits of technology

It significantly reduces the resistance value, improves ion transfer efficiency, mechanical strength and stability, and extends the number of cycle charge and discharge times of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833726A_ABST
    Figure CN119833726A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte. The composite solid electrolyte comprises lithium lanthanum zirconium oxide powder and a lithium phosphate-containing protective layer. The average particle size of the lithium lanthanum zirconium oxide powder is less than 500nm. And the lithium phosphate-containing protective layer coats the outer surface of the lithium lanthanum zirconium oxide powder. The composite solid electrolyte is based on the solid electrolyte, so that the defects of liquid electrolyte volatilization, leakage, instability in high-temperature use and the like can be avoided. The composite solid electrolyte also comprises a lithium phosphate-containing protective layer, so that the composite solid electrolyte has the property close to a liquid state and / or a colloidal state, and the wettability and the like are improved. The composite solid electrolyte has good performance, such as high ion transfer efficiency, high mechanical strength, high stability, low resistance value and the like, and does not deteriorate after being used for a long time. And the composite solid electrolyte is easy for subsequent operation and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite solid electrolyte and a method for manufacturing the same. Background Art

[0002] Traditional liquid electrolytes have many disadvantages, such as easy volatilization and leakage of liquids. When used at high temperatures, liquid electrolytes are also prone to unexpected changes due to instability, such as explosions. Solid electrolytes have higher stability than liquid electrolytes, such as higher thermal, electrochemical and mechanical stability. Therefore, more and more fields use solid electrolytes to replace liquid electrolytes, such as electric vehicles and energy storage fields with high safety requirements. However, solid electrolytes may have high resistance values, resulting in poor ion transfer rates of solid electrolytes used in batteries. Therefore, it is necessary to develop a composite solid electrolyte and a method for manufacturing the same, which can not only solve the problems of liquid electrolytes, but also significantly reduce the resistance value and not damage the performance of the composite solid electrolyte during the manufacturing process. Summary of the invention

[0003] The present invention provides a composite solid electrolyte. The composite solid electrolyte includes lithium lanthanum zirconium oxide powder and a lithium phosphate-containing protective layer. The average particle size of the lithium lanthanum zirconium oxide powder is less than 500nm. The lithium phosphate-containing protective layer covers the outer surface of the lithium lanthanum zirconium oxide powder.

[0004] In some embodiments, the lithium lanthanum zirconium oxide powder is covalently bonded to the lithium phosphate in the lithium phosphate-containing protective layer.

[0005] In some embodiments, the weight ratio of the lithium lanthanum zirconium oxide powder to the lithium phosphate in the lithium phosphate-containing protective layer is 2:1 to 3:1.

[0006] In some embodiments, the content of lithium carbonate in the lithium phosphate-containing protective layer is substantially equal to zero.

[0007] The present invention also provides a composite solid electrolyte. The composite solid electrolyte includes lithium lanthanum zirconium oxide nanopowder, a lithium phosphate-containing protective layer and a fluorine-containing colloid. The lithium phosphate-containing protective layer coats the outer surface of the lithium lanthanum zirconium oxide nanopowder. The fluorine-containing colloid includes a fluorine-containing polyolefin, and the lithium lanthanum zirconium oxide nanopowder coated with the lithium phosphate-containing protective layer is distributed in the fluorine-containing colloid.

[0008] In some embodiments, the viscosity of the fluorinated colloid is from 1000 cps to 5000 cps.

[0009] The present invention also provides a method for manufacturing a composite solid electrolyte. The method includes the following operations: grinding lithium lanthanum zirconium oxide to form lithium lanthanum zirconium oxide powder. Mixing the lithium lanthanum zirconium oxide powder with phosphoric acid to form a lithium phosphate protective layer to coat the outer surface of the lithium lanthanum zirconium oxide powder through an acid-base reaction.

[0010] In some embodiments, the lithium lanthanum zirconium oxide powder has an average particle size less than 500 nm.

[0011] In some embodiments, the end point of the acid-base reaction is a pH value of 4.5 to 6.

[0012] In some embodiments, the method further comprises mixing the lithium lanthanum zirconium oxide powder coated with the lithium phosphate-containing protective layer with a fluorine-containing colloid, wherein the fluorine-containing colloid comprises a fluorine-containing polyolefin. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] When reading the drawings of the present invention, it is recommended to understand various aspects of the present invention from the detailed description below. It should be noted that various feature sizes may not be drawn to scale according to standard industry practices. In addition, various feature sizes may be increased or decreased to make the discussion clear. In addition, in order to simplify the drawings, conventional features and structures will be depicted in a simple schematic manner in the drawings.

[0014] Figure 1 is a flow chart of a method for manufacturing a composite solid electrolyte according to some embodiments of the present invention.

[0015] Figure 2 4 is a comparison diagram of Raman spectra of some embodiments and some comparative examples according to the present invention.

[0016] Figure 3 This is a comparison table showing the change in viscosity of composite solid electrolytes according to some embodiments and some comparative examples of the present invention as a function of the rotor speed of the rheometer.

[0017] Figure 4A and Figure 4B The figures are comparison diagrams of optical micrographs of some embodiments and some comparative examples according to the present invention. DETAILED DESCRIPTION

[0018] In order to make the description of the content of the present invention more detailed and complete, the following is an illustrative description of the embodiments and specific embodiments. This does not limit the embodiments of the content of the present invention to the only form. The embodiments of the content of the present invention can be combined or replaced with each other in beneficial situations, and other embodiments can be added without further description.

[0019] The terms "approximately", "approximately", "close to", "substantially" or "substantially" used in the present invention include the numerical values, features and the deviation ranges of the numerical values ​​and features that can be understood by technicians in the relevant technical field. For example, taking into account the errors of numerical values ​​and features, the aforementioned terms may represent values ​​within one or more standard deviations of the numerical values ​​(e.g., values ​​within ±30%, ±20%, ±15%, ±10% or ±5%), or represent the deviations covered by the features in practical operations (e.g., the description of "substantially parallel" may mean close to parallel in practice rather than perfect parallel in ideal). In addition, an acceptable deviation range may be selected according to measurement properties or other properties, rather than applying one deviation range to all numerical values ​​and features.

[0020] The present invention provides a composite solid electrolyte. The composite solid electrolyte includes lithium lanthanum zirconium oxide powder and a lithium phosphate-containing protective layer. The average particle size of the lithium lanthanum zirconium oxide powder is less than 500nm. The lithium phosphate-containing protective layer coats the outer surface of the lithium lanthanum zirconium oxide powder. The composite solid electrolyte of the present invention has good performance (such as high ion transfer efficiency, high mechanical strength, high stability and low resistance value, etc.), and can be used for a long time without deterioration (thereby increasing the number of charge and discharge cycles used in the battery, etc.). The above-mentioned composite solid electrolyte is described in detail below according to the implementation method.

[0021] First, the lithium lanthanum zirconium oxide powder is described. The powdery lithium lanthanum zirconium oxide powder improves the performance of the lithium lanthanum zirconium oxide powder by increasing the surface area, and makes it easier and more complete to coat the lithium phosphate-containing protective layer described below on the surface of the lithium lanthanum zirconium oxide powder to provide protection for the lithium lanthanum zirconium oxide powder. In some embodiments, the average particle size or average diameter of the lithium lanthanum zirconium oxide powder (which can be measured by any feasible method, such as a particle size analyzer) is preferably less than 500nm, for example, less than 500nm, less than 250nm or less than 100nm. In some embodiments, the average particle size or average diameter of the lithium lanthanum zirconium oxide powder is preferably greater than 50nm. If the average particle size or average diameter is too large, it may not have a large enough surface area to significantly improve the performance of the lithium lanthanum zirconium oxide powder, and it may not be possible to ensure that the lithium phosphate-containing protective layer completely coats the surface of the lithium lanthanum zirconium oxide powder to provide sufficient protection. If the average particle size or average diameter is too small, it may not have a significant beneficial effect and may cause process waste.

[0022] The lithium lanthanum zirconium oxide powder is further described. In some embodiments, the lithium lanthanum zirconium oxide powder includes Li x Ln3Z y O 12 , wherein x is 3 to 7.5, y is 0 to 2, and preferably Li7La3Zr2O 12The lithium lanthanum zirconium oxide powder has a good crystal phase and high crystal purity to improve performance including ion transfer efficiency, mechanical strength and stability. In some embodiments, the lithium lanthanum zirconium oxide powder is substantially a cubic crystal structure. In some embodiments, the lithium lanthanum zirconium oxide powder is substantially a garnet crystal structure.

[0023] Next, the lithium phosphate-containing protective layer is described. The lithium phosphate-containing protective layer coats the outer surface of the lithium lanthanum zirconium oxide powder to protect the lithium lanthanum zirconium oxide powder located in the inner layer through the lithium phosphate component therein. In detail, the lithium phosphate-containing protective layer substantially separates the lithium lanthanum zirconium oxide powder from water vapor and carbon dioxide in the air. Therefore, the lithium lanthanum zirconium oxide powder is prevented from being exposed to the air to cause surface adsorption and / or generate impurities, thereby affecting the performance of the lithium lanthanum zirconium oxide powder. For example, water vapor and carbon dioxide in the air may generate lithium hydroxide, lithium carbonate, etc. on the surface of the lithium lanthanum zirconium oxide powder, causing the surface resistance value of the lithium lanthanum zirconium oxide powder to increase, thereby reducing the number of times the composite solid electrolyte is recycled. In addition to the role of protecting and stabilizing the lithium lanthanum zirconium oxide powder, the lithium phosphate-containing protective layer itself also has the role of improving the performance of the composite solid electrolyte due to the presence of lithium phosphate, for example, by increasing the wettability of the lithium lanthanum zirconium oxide powder to improve the ion transfer efficiency, and thus reduce the resistance value of the surface of the lithium lanthanum zirconium oxide powder. In some embodiments, the lithium phosphate-containing protective layer (and the lithium phosphate therein) uniformly coats the surface of the lithium lanthanum zirconium oxide powder to provide better protection, stability and improved performance. In some embodiments, the lithium phosphate-containing protective layer (and the lithium phosphate therein) completely coats the entire surface of the lithium lanthanum zirconium oxide powder to provide better protection, stability and improved performance. In some embodiments, the thickness of the lithium phosphate-containing protective layer (and the lithium phosphate therein) is preferably 30nm to 45nm, such as 30nm, 33nm, 37nm, 42nm or 45nm. In some embodiments, the lithium lanthanum zirconium oxide powder and the lithium phosphate in the lithium phosphate-containing protective layer are connected to each other by covalent bonds. In some embodiments, the weight ratio of lithium lanthanum zirconium oxide powder to lithium phosphate in the lithium phosphate-containing protective layer is preferably 2:1 to 3:1, such as 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3:1, etc. In some embodiments, the content of lithium carbonate in the lithium phosphate-containing protective layer is substantially equal to 0, so as to effectively suppress the negative effects caused by lithium carbonate. In some embodiments, the lithium phosphate-containing protective layer preferably has a pH value of 4.5 to 6, such as 4.5, 5, 5.5 or 6, so as to have a sufficiently high lithium phosphate component and a sufficiently low lithium carbonate component.

[0024] The present invention also provides a composite solid electrolyte. The composite solid electrolyte includes lithium lanthanum zirconium oxide nanopowder, a lithium phosphate-containing protective layer and a fluorine-containing colloid. The lithium phosphate-containing protective layer coats the outer surface of the lithium lanthanum zirconium oxide nanopowder. The fluorine-containing colloid includes a fluorine-containing polyolefin, and a lithium lanthanum zirconium oxide nanopowder coated with a lithium phosphate-containing protective layer is distributed in the fluorine-containing colloid. The composite solid electrolyte of the present invention has good performance as described above (such as high ion transfer efficiency, high mechanical strength, high stability and low resistance value, etc.), and can be used for a long time without deterioration (thereby increasing the number of cycle charge and discharge times used in the battery, etc.), and the performance is further improved by distributing the lithium lanthanum zirconium oxide nanopowder coated with a lithium phosphate-containing protective layer in the fluorine-containing colloid. Next, the aforementioned composite solid electrolyte is described in detail according to the implementation method.

[0025] First, the lithium lanthanum zirconium oxide nanopowder and the lithium phosphate-containing protective layer are explained. The lithium lanthanum zirconium oxide nanopowder and the lithium phosphate-containing protective layer are basically the same as the lithium lanthanum zirconium oxide powder and the lithium phosphate-containing protective layer mentioned above, so the details can be referred to above and will not be repeated here. However, the lithium phosphate in the lithium phosphate-containing protective layer also has the effect of improving the performance of the fluorine-containing colloid to be described below. In detail, the lithium phosphate in the lithium phosphate-containing protective layer can inhibit the defluorination reaction of the fluorine-containing polyolefin in the fluorine-containing colloid and deterioration, thereby avoiding the increase in the viscosity of the fluorine-containing colloid and the difficulty in subsequent processes, such as avoiding coating difficulties and avoiding increasing the temperature required for the process due to coating difficulties.

[0026] Next, the fluorinated colloid is described. The fluorinated colloid improves the wettability of the lithium lanthanum zirconium oxide nanopowder coated with the lithium phosphate protective layer, thereby reducing the resistance value. In addition, the fluorinated colloid also improves the adhesion and flexibility due to the polymer properties of the fluorinated polyolefin therein, so that it can be well adhered to, for example, electrodes and is suitable for flexible batteries. In some embodiments, the viscosity of the fluorinated colloid (which can be measured by any feasible method, such as Figure 3The viscosity of the fluorinated polyolefin is preferably 1000 cps (or centipoise (cP)) to 5000 cps, such as 1000 cps, 2000 cps, 3000 cps, 4000 cps or 5000 cps, so as to avoid the high viscosity which may cause difficulty in subsequent processes and the low viscosity which may cause poor adhesion or flexibility. In some embodiments, the weight average molecular weight of the fluorinated polyolefin is preferably 400,000 Da to 2,000,000 Da, such as 400,000 Da, 800,000 Da, 1,200,000 Da, 1,600,000 Da or 2,000,000 Da. In some embodiments, the preferred fluorinated polyolefin includes polyvinylidene fluoride. In some embodiments, the weight ratio of lithium lanthanum zirconium oxide nanopowder to fluorinated polyolefin is preferably 30% to 50%, such as 30%, 35%, 40%, 45% or 50%. If the weight ratio of lithium lanthanum zirconium oxide nanopowder to fluorinated polyolefin is too small, the content of lithium lanthanum zirconium oxide nanopowder as the main component of the electrolyte may be too small, thereby reducing the ion transfer efficiency, and too much fluorinated polyolefin may not have the effect of significantly improving wettability, adhesion and flexibility, etc., resulting in process waste. If the weight ratio of lithium lanthanum zirconium oxide nanopowder to fluorinated polyolefin is too large, the lithium lanthanum zirconium oxide nanopowder may lack sufficient wettability, adhesion and flexibility provided by fluorinated polyolefin, and it may be impossible to further reduce the resistance value between lithium lanthanum zirconium oxide nanopowders and increase the applicability of lithium lanthanum zirconium oxide nanopowders.

[0027] The present invention also provides a method for manufacturing the above composite solid electrolyte. The method includes the following operations. Grinding lithium lanthanum zirconium oxide to form lithium lanthanum zirconium oxide powder. Mixing lithium lanthanum zirconium oxide powder and phosphoric acid to form a lithium phosphate protective layer to coat the outer surface of the lithium lanthanum zirconium oxide powder through an acid-base reaction. The composite solid electrolyte manufactured by the method of the present invention not only has good performance as described above (such as high ion transfer efficiency, high mechanical strength, high stability and low resistance value, etc.) and can be used for a long time without deterioration (thereby increasing the number of charge and discharge cycles used in the battery, etc.), but also avoids the destruction of the crystal phase, effectively modifies the surface of the powder, and the process is simple and fast. Next, refer to Figure 1 The method 100 is described in detail according to the implementation scheme.

[0028] exist Figure 1In operation 101 of method 100, lithium lanthanum zirconium oxide is ground to form lithium lanthanum zirconium oxide powder. The lithium lanthanum zirconium oxide is substantially the same as the lithium lanthanum zirconium oxide powder and lithium lanthanum zirconium oxide nanopowder described above, but the size may be larger, and after completing operation 101, the size is less than 500nm as described above. In some embodiments, grinding the lithium lanthanum zirconium oxide includes wet grinding the lithium lanthanum zirconium oxide in an organic polar solvent. In some embodiments, the organic polar solvent includes N,N-dimethylacetamide, ethanol, isopropanol, or a combination thereof. In some embodiments, grinding the lithium lanthanum zirconium oxide is performed using a bead mill. In some embodiments, the barrel of the bead mill includes lithium lanthanum zirconium oxide, an organic polar solvent, an agitator, and grinding beads, wherein the agitator drives the grinding beads to rotate during the stirring process, and the friction and impact force between the grinding beads and the lithium lanthanum zirconium oxide reduce the size of the lithium lanthanum zirconium oxide and evenly disperse it. In some embodiments, the rotation speed of the bead mill is 2000 rpm to 4000 rpm, such as 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm or 4000 rpm, etc. In some embodiments, the temperature for performing operation 101 is room temperature, such as 20° C. to 30° C., such as 20° C., 22° C., 24° C., 26° C., 28° C. or 30° C., etc. In some embodiments, operation 101 is performed until the lithium lanthanum zirconium oxide is ground to form a lithium lanthanum zirconium oxide powder having an average particle size or an average diameter of less than 500 nm.

[0029] exist Figure 1In operation 102 of method 100, lithium lanthanum zirconium oxide powder and phosphoric acid are mixed to form a lithium phosphate-containing protective layer to cover the outer surface of the lithium lanthanum zirconium oxide powder through an acid-base reaction. In some embodiments, the acid-base reaction includes reacting phosphoric acid with lithium carbonate that may be generated on the surface of the lithium lanthanum zirconium oxide powder to form a lithium phosphate-containing protective layer on the surface of the lithium lanthanum zirconium oxide powder. By using an acid-base reaction, not only is a lithium phosphate-containing protective layer formed on the surface of the lithium lanthanum zirconium oxide powder, but also the crystalline phase of the lithium lanthanum zirconium oxide powder can be prevented from being damaged by water by removing lithium carbonate by dissolving lithium carbonate on the surface of the lithium lanthanum zirconium oxide powder with water. In addition, compared with the use of grinding and polishing techniques, converting lithium carbonate into lithium phosphate through an acid-base reaction can more comprehensively remove lithium carbonate on the powder and thereby form an effective lithium phosphate-containing protective layer. In some embodiments, the concentration of phosphoric acid is preferably greater than or equal to 85wt%, greater than or equal to 90wt%, or greater than or equal to 95wt%, so as to be sufficient for acid-base reaction and reduce the damage that water may cause to the crystalline phase. In some embodiments, the weight ratio of lithium lanthanum zirconium oxide powder to phosphoric acid in operation 102 is preferably 0.5:1 to 10:1, such as 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc., and more preferably 0.5:1 to 4:1. In some embodiments, mixing lithium lanthanum zirconium oxide powder and phosphoric acid is performed by using a bead mill. In some embodiments, the rotation speed of the bead mill is 100 rpm to 2000 rpm, such as 100 rpm, 500 rpm, 1000 rpm, 1500 rpm or 2000 rpm. In some embodiments, operation 102 is directly performed after operation 101 using the same bead mill. In some embodiments, after the lithium lanthanum zirconium oxide powder having an average particle size or an average diameter of less than 500 nm is formed in operation 101, operation 102 is directly performed (i.e., there may be no other operation between operation 101 and operation 102 or the interval time between operation 101 and operation 102 is substantially equal to 0). In some embodiments, the temperature for performing operation 102 is room temperature, such as 20°C to 30°C, such as 20°C, 22°C, 24°C, 26°C, 28°C or 30°C. In some embodiments, operation 102 is performed until the reaction end point of the acid-base reaction is preferably a pH value of 4.5 to 6, such as 4.5, 5, 5.5 or 6, so as to have a sufficiently high lithium phosphate component and a sufficiently low lithium carbonate component.

[0030] In some embodiments, method 100 further comprises mixing a lithium lanthanum zirconium oxide powder coated with a lithium phosphate-containing protective layer with a fluorine-containing colloid after operation 102, wherein the fluorine-containing colloid comprises a fluorine-containing polyolefin. For detailed features of the fluorine-containing colloid, refer to the above and will not be repeated here. In some embodiments, mixing the lithium lanthanum zirconium oxide powder coated with a lithium phosphate-containing protective layer with the fluorine-containing colloid is performed in an organic solvent. In some embodiments, the organic solvent comprises N,N-dimethylacetamide.

[0031] Next, the composite solid electrolyte and the method for manufacturing the same according to the present invention are described according to detailed embodiments. To simplify the description, only some detailed embodiments are provided below, and thus the scope of the present invention should not be limited thereto.

[0032] Figure 2 Line C1 is a Raman spectrum of a composite solid electrolyte according to some embodiments of the present invention. Figure 2 Line C2 is a Raman spectrum of a composite solid electrolyte according to some comparative examples of the present invention but not including a lithium phosphate protective layer. Figure 2 It can be seen that line C1 has a clear Raman shift for lithium phosphate (indicated by ▽ in the figure) and almost no Raman shift corresponding to lithium carbonate. Compared with line C1, line C2 has a clear Raman shift for lithium carbonate (indicated by * in the figure). It should be noted that Figure 2 The Raman spectrum comparison diagram of line C1 and line C2 is compared by mathematical normalization operation, so the intensity is unitless and marked in arbitrary units.

[0033] Figure 3 The table is a comparison of the viscosity changes with the rheometer rotor speed according to some embodiments and some comparative examples, wherein the embodiments are the viscosity changes of the composite solid electrolyte of the present invention with the rheometer rotor speed, and the comparative examples are the viscosity changes of the composite solid electrolyte corresponding to the present invention but not including the lithium phosphate protective layer with the rheometer rotor speed. Figure 3 It can be seen from the comparison that since the present invention includes a lithium phosphate protective layer, the fluorine-containing colloid is not easily fluorinated, so the viscosity is significantly reduced, and subsequent operations are easy, such as easy coating and no need to increase the temperature to facilitate coating.

[0034] Figure 4A is an optical micrograph of a thin film formed by a composite solid electrolyte according to some embodiments of the present invention. Figure 4B 1 is an optical micrograph of a thin film formed by a composite solid electrolyte according to some comparative examples of the present invention but not including a lithium phosphate protective layer. Figure 4A and Figure 4BThe comparison shows that the film of the embodiment is smooth and easy to be used in subsequent processes. The film of the comparative example has obvious particles.

[0035] The composite solid electrolyte and the method for manufacturing the same of the present invention have many advantages. For example, the composite solid electrolyte can avoid the disadvantages of liquid electrolyte volatilization, leakage and instability when used at high temperatures based on solid electrolyte. The composite solid electrolyte also has properties close to liquid and / or colloidal properties due to the inclusion of a lithium phosphate protective layer and / or a fluorine-containing colloid, thereby improving wettability. The composite solid electrolyte has good performance, such as high ion transfer efficiency, high mechanical strength, high stability and low resistance, and no deterioration after long-term use. The composite solid electrolyte is easy to operate and apply later. The manufacturing method is easy to implement and is simple and fast.

[0036] The present invention is described in considerable detail with respect to some embodiments, but other embodiments are possible, and thus the scope and spirit of the appended claims should not be limited by the description of the embodiments contained in this summary.

[0037] It is obvious to those skilled in the art that modifications and changes may be made to the content of the present invention without departing from the scope and spirit of the content of the present invention. As long as the aforementioned modifications and changes fall within the scope and spirit of the appended claims, the content of the present invention covers these modifications and changes.

[0038]

Explanation of symbols

[0039] 100: Methods

[0040] 101, 102: Operation

[0041] C1, C2: lines.

Claims

1. A composite solid electrolyte, characterized in that: include: Lithium lanthanum zirconium oxide powder, wherein the average particle size of the lithium lanthanum zirconium oxide powder is less than 500 nm; as well as A lithium phosphate protective layer is provided, wherein the lithium phosphate protective layer covers the outer surface of the lithium lanthanum zirconium oxide powder.

2. The composite solid electrolyte according to claim 1, wherein the lithium lanthanum zirconium oxide powder is connected to the lithium phosphate in the lithium phosphate-containing protective layer by a covalent bond.

3. The composite solid electrolyte according to claim 1 or 2, wherein the weight ratio of the lithium lanthanum zirconium oxide powder to the lithium phosphate in the lithium phosphate-containing protective layer is 2:1 to 3:

1. 4 . The composite solid electrolyte according to claim 1 , wherein the content of lithium carbonate in the lithium phosphate-containing protective layer is substantially equal to 0.

5. A composite solid electrolyte, characterized in that: include: Lithium lanthanum zirconium oxide nanopowder; A lithium phosphate-containing protective layer, wherein the lithium phosphate-containing protective layer covers the outer surface of the lithium lanthanum zirconium oxide nanopowder; as well as The fluorine-containing colloid comprises fluorine-containing polyolefin, and the lithium lanthanum zirconium oxide nanopowder coated with the lithium phosphate-containing protective layer is distributed in the fluorine-containing colloid. The composite solid electrolyte according to claim 5 , wherein the viscosity of the fluorine-containing colloid is 1000 cps to 5000 cps.

7. A method for manufacturing a composite solid electrolyte, characterized in that: include: grinding lithium lanthanum zirconium oxide to form lithium lanthanum zirconium oxide powder; as well as The lithium lanthanum zirconium oxide powder is mixed with phosphoric acid to form a lithium phosphate protective layer through an acid-base reaction to cover the outer surface of the lithium lanthanum zirconium oxide powder.

8. The method according to claim 7, wherein the lithium lanthanum zirconium oxide powder has an average particle size less than 500 nm.

9. The method according to claim 7 or 8, wherein the reaction end point of the acid-base reaction is a pH value of 4.5 to 6.

10. The method according to claim 7, wherein: The method also includes mixing the lithium lanthanum zirconium oxide powder coated with the lithium phosphate-containing protective layer and a fluorine-containing colloid, wherein the fluorine-containing colloid includes a fluorine-containing polyolefin.

Citation Information

Cited By

  • Polyformaldehyde-based composite solid electrolyte membrane and preparation method thereof

    CN122267270A